Analyzing Neuronal Mitochondria in vivo Using Fluorescent Reporters in Zebrafish - Mandal, Amrita; Pinter, Katherine; Drerup, Catherine M. (Frontiers in Cell and Developmental Biology, 2018)
Despite their importance for cellular viability, the actual life history and properties of mitochondria in neurons are still unclear. These organelles are distributed throughout the entirety of the neuron and serve many functions, including: energy production (ATP), iron homeostasis and processing, calcium buffering, and metabolite production, as well as many other lesser known activities. Given their importance, understanding how these organelles are positioned and how their health and function is maintained is critical for many aspects of cell biology. This is best illustrated by the diverse disease literature which demonstrates that abnormal mitochondrial movement, localization, size, or function often correlates with neural pathology. In the following methods article, we will describe the techniques and tools we have optimized to directly visualize mitochondria and analyze mitochondrial lifetime, health, and function in neurons in vivo using fluorescent reporters in the zebrafish. The zebrafish system is ideal for in vivo studies of mitochondrial biology as: 1) neuronal circuits develop rapidly, within days; 2) it is genetically accessible; and 3) embryos and larvae are translucent allowing imaging in a completely intact vertebrate nervous system. Using these tools and techniques, the field is poised to answer questions of mitochondrial biology in the context of neuronal health and function in normal and disease states.